Succinate metabolism: a promising therapeutic target for inflammation, ischemia/reperfusion injury and cancer - Zhang, Wenhui; Lang, Ren (Frontiers in Cell and Developmental Biology, 2023)
Succinate serves as an essential circulating metabolite within the tricarboxylic acid (TCA) cycle and functions as a substrate for succinate dehydrogenase (SDH), thereby contributing to energy production in fundamental mitochondrial metabolic pathways.succinate concentrations have been associated with pathological states, including chronic inflammation, ischemia/reperfusion (IR) injury, and cancer, resulting from the exaggerated response of specific immune cells, thereby rendering it a central area of investigation. Recent studies have elucidated the pivotal involvement of succinate and SDH in immunity beyond metabolic processes, particularly in the context of cancer. Current scientific endeavors are concentrated on comprehending the functional repercussions of metabolic modifications, specifically pertaining to succinate and SDH, in immune cells operating within a hypoxic milieu. The efficacy of targeting succinate and SDH alterations to manipulate immune cell functions in hypoxia-related diseases have been demonstrated. Consequently, a comprehensive understanding of succinate's role in metabolism and the regulation of SDH is crucial for effectively targeting succinate and SDH as therapeutic interventions to influence the progression of specific diseases. This review provides a succinct overview of the latest advancements in comprehending the emerging functions of succinate and SDH in metabolic processes. Furthermore, it explores the involvement of succinate, an intermediary of the TCA cycle, in chronic inflammation, IR injury, and cancer, with particular emphasis on the mechanisms underlying succinate accumulation. This review critically assesses the potential of modulating succinate accumulation and metabolism within the hypoxic milieu as a means to combat various diseases. It explores potential targets for therapeutic interventions by focusing on succinate metabolism and the regulation of SDH in hypoxia-related disorders.